Relative efficiency assessment of projects using data envelopment analysis - Ku-Mahamud, Ku Ruhana; Ahmad, Faudziah; Abd Ghani, Nor Farzana; Mat Kasim, Maznah; Abdullah, Fader (2011)
This paper presents an evaluation of project efficiencies of 39 companies using data Envelopment Analysis.In-Fusion Solutions Sdn. Bhd. was chosen as the case study and data were collected from primary and secondary sources. Primary data were obtained through interviews conducted with personnel from the main office and the company branch in Chennai, India.Secondary data were obtained from published and unpublished documents.Secondary data consisted of information technology completed projects which consist of three inputs and an output.These include labor cost, material cost, project duration, and project contract value.Experimental result was able to identify efficient and inefficient projects.Results obtained showed that there were three efficient projects and the remaining projects were otherwise.Peer group analysis was also conducted to compare projects that are inefficient with efficient projects which belonged to a reference set.